Recent Publications (Quarterly Journal of Economics, 1949)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 63, Issue 2, May 1949, Pages 282–287, https://doi.org/10.1093/qje/63.2.282 Published: 01 May 1949